Decoding Circadian Rhythm and Epileptic Activities: Clues From Animal Studies - Xu, Cenglin; Yu, Jie; Ruan, Yeping; Wang, Yi; Chen, Zhong (Frontiers in Neurology, 2020)
The relationship between circadian rhythm and epilepsy has been recognized for decades. Yet many questions underlying the complex mechanisms of their interaction remain elusive. A better understanding on this topic allows the development of accurate seizure-detection algorithm and alternative precise therapeutic strategies. Preclinical laboratory studies based on epileptic animal models, with controllable epileptogenic pathology and an array of intervention strategies, shed light on the bidirectional effects between circadian rhythm and epileptic seizures as well as their underlying mechanisms. Here, we reviewed findings on the interaction between circadian rhythm and epileptic seizures in the preclinical setting. We present the possible mechanisms at molecular, cellular and circuitry levels. We propose that future experimental designs should take into account the relationship between circadian rhythm and epilepsy as well as the underlying mechanisms in different types of animal models, which may have a translational significance as stepping stones for clinical benefits.